Voorbij de verzuiling? - Rooy, P. de (BMGN - Low Countries Historical Review, 2001)
J.C.H. Blom, J. Talsma, De verzuiling voorbij. Godsdienst, stand en natie in de lange negentiende eeuw Beyond Pillarization?This paper discusses a group of studies carried out at the University of Amsterdam on pillarization at a local level. Participants in this research programme concluded that additional research on the subject would be beneficial as it would provide a better understanding of how religion, social hierarchy and state- and nation-building developed. For this purpose, a brief outline of the pillarization process on a national level (1816-1917) with some concluding remarks is given: all pillars were different (in origin, structure and function); pillarization can only be understood if it is viewed as a dynamic process of rivalry; and, the liberals did not succeed in pillar formation, perhaps because they placed too much trust in their own position within the state, the law and the university. Pillarization is the term used to describe a vertical social stratification system in the Netherlands based on religious denomination.